EFEKTIFITAS PERMAINAN PENJEPIT UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK TUNAGRAHITA SEDANG - Mardhatillah - (Universitas Negeri Padang, 2014)
Abstract:This research was motivated by the problems that researchers in the field found that mental retardation was a fourth grade student intellectual disability in SLB Fan Redha Padang who have difficulty in fine motor skills. The ability of re intellectual disability searchers wanted to increase the students ability to take peanut seeds using three fingers. This study used experimental approach in the form of single subjeck research ( study a single subject ), with ABA design and data analiys techniques using visual analysis grafick. The subjeck were moderate mental retardation children. Assesment of this research is to measure the percentage of student in the fine motor skills throught the game taking beans clamp. Keyword: Permainan penjepit ; Meningkatkan motorik halus anak tunagrahita sedang